Revision of the genus Heterocoelia Dahlbom from China, with a key to the Oriental species (Hymenoptera: Bethylidae) - Xu, Zaifu; He, Junhua (Zootaxa, 2006)
The males of two new species of Heterocoelia from China: H. zhaoi n. sp. and H. sinensis n. sp. are described and illustrated. A key to Chinese Heterocoelia is provided. The type specimens are deposited in the Department of Plant Protection, Zhejiang University, China.